Implementing Engaging Strategies to Cultivate Study Habits and Propel Academic Achievement among Secondary School Students - ADEOYE, Moses Adeleke; PARAMOLE, Oyeronke Christiana; JOLAOYE, Joshua Durotoye; JIBRIL, Ayuba Olaniyi (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2023)
Effective study habits are essential for academic success among secondary school students. However, many students struggle to develop and maintain effective study habits, leading to poor academic performance. The paper explores the significance of building bridges to success by implementing engaging strategies to cultivate study habits and propel academic achievement in secondary school students. It highlights the theoretical framework behind this approach and emphasizes the importance of study habits in the lives of students. Additionally, the paper presents evidence-based strategies and interventions that can be applied in educational settings to enhance students' study habits and academic performance. The paper also provides practical strategies that educators can employ to foster a supportive learning environment and teach effective study techniques. Additionally, it discusses the implementation of engaging strategies in the classroom, such as active learning techniques, technology integration, and collaborative learning. Lastly, the paper addresses the importance of assessing and monitoring students' progress to ensure the effectiveness of these strategies. In conclusion, cultivating study habits and promoting academic achievement among secondary school students can foster a positive and engaging learning environment and students can develop the necessary skills and habits to excel academically.